(untitled) (London Journal of Engineering Research, 2026)
Context: Many areas of modern electronic equipment, such as medical, automotive, portable, and special-purpose electronics, place increased demands on mass and volume. These devices often have irregular volume structures for accommodating electronic components. Therefore, 3D printed circuit boards are ideal for implementing such designs, and improving their efficiency, as well as optimizing the selection of mounting types, are pressing challenges. Objective: The aim of this work is to develop a 3D printed circuit board method that is efficient in production and use, as well as a method for objectively selecting the optimal PCB option from the existing variety when designing miniature electronic equipment. Method: The design and manufacturing method for manufacturing rigid-flexible printed circuit boards is based on traditional PCB manufacturing methods with an appropriate addition that allows for the achievement of three-dimensional design properties. The method for selecting a 3D printed circuit board option consists of two parts: a heuristic method and passive game theory. Results: A design and engineering method for producing a rigid-flexible printed circuit board has been developed. Its main feature is its fabrication on a single base—a rigid printed circuit board. A sequence of steps for implementing a heuristic method is presented, and 3D printed circuit assembly metrics and their characteristics are developed, serving as input for experts selecting the optimal option. A method for using passive game theory to solve the same problem of selecting a3D printed circuit board option is presented. A number of formalized metrics and coefficients have been developed for this purpose. Conclusions: This paper addresses the problem of developing methods for creating printed circuit boards forthree-dimensional printed wiringand selecting optimal electrical connection designs for electronic equipment design. The practical value of the proposed methods lies in their ready-to-use nature.